A Modified Taylor Series Expansion Method for the Second Order Linear Volterra Integro-Differential Equation - Navarasuchitr, Itthithep; Jaitrong, Jaturong (Science Essence Journal, 2023)
In this paper, we used a modified Taylor series expansion method for approximating the solutions of linear second order Volterra Integro-Differential Equation (VIDE). This method transforms the equation to linear system equations that can be solved easily with computer programing. Finally, we showed the efficiency of this method with numerical examples by comparing the approximate solutions with exact solutions.